Sister Dehalobacter Genomes Reveal Specialization in Organohalide Respiration and Recent Strain Differentiation Likely Driven by Chlorinated Substrates - Tang, Shuiquan; Wang, Po Hsiang; Higgins, Steven A.; Löffler, Frank E.; Edwards, Elizabeth A. (Frontiers in Microbiology, 2016)
The genomes of two closely related Dehalobacter strains (strain CF and strain DCA) were assembled from the metagenome of an anaerobic enrichment culture that reductively dechlorinates chloroform (CF), 1,1,1-trichloroethane (1,1,1-TCA) and 1,1-dichloroethane (1,1-DCA). The 3.1 Mbp genomes of strain CF (that dechlorinates CF and 1,1,1-TCA) and strain DCA (that dechlorinates 1,1-DCA) each contain 17 putative reductive dehalogenase homologous (rdh) genes. These two genomes were systematically compared to three other available organohalide-respiring Dehalobacter genomes (Dehalobacter restrictus strain PER-K23, Dehalobacter sp. strain E1 and Dehalobacter sp. strain UNSWDHB), and to the genomes of Dehalococcoides mccartyi strain 195 and Desulfitobacterium hafniense strain Y51. This analysis compared 42 different metabolic and physiological categories. The genomes of strains CF and DCA share 90% overall average nucleotide identity and greater than 99.8% identity over a 2.9 Mbp alignment that excludes large insertions, indicating that these genomes differentiated from a close common ancestor. This differentiation was likely driven by selection pressures around two orthologous reductive dehalogenase genes, cfrA and dcrA, that code for the enzymes that reduce CF or 1,1,1-TCA and 1,1-DCA. The many reductive dehalogenase genes found in the five Dehalobacter genomes cluster into two small conserved regions and were often associated with Crp/Fnr transcriptional regulators. Specialization is on-going on a strain-specific basis, as some strains but not others have lost essential genes in the Wood-Ljungdahl (strain E1) and corrinoid biosynthesis pathways (strains E1 and PER-K23). The gene encoding phosphoserine phosphatase, which catalyzes the last step of serine biosynthesis, is missing from all five Dehalobacter genomes, yet D. restrictus can grow without serine, suggesting an alternative or unrecognized biosynthesis route exists. In contrast to Dehalococcoides mccartyi, a complete heme biosynthesis pathway is present in the five Dehalobacter genomes. This pathway corresponds to a newly described alternative heme biosynthesis route first identified in Archaea. This analysis of organohalide-respiring Firmicutes and Chloroflexi reveals profound evolutionary differences despite very similar niche-specific metabolism and function.